Design and Implementation of English Listening Teaching Based on a Wireless Communication Microprocessor and Virtual Environment - Li Liu (Hindawi Limited, 2021)
This paper presents an in-depth analysis and research on teaching English listening through a wireless communication microprocessor combined with a virtual environment and designs and implements an English listening teaching experiment. Based on an in-depth understanding of wireless communication algorithms, this thesis extends the instruction set based on the general-purpose compact instruction set computer architecture (RISC) for common operations in wireless communication algorithms, adding new instructions such as multiplication and addition and bit inversion. The microprocessor has an increase in the number of execution clocks for wireless algorithm processing. The processor is extended with an interrupt interface to facilitate information interaction between the processor and the external environment to achieve coordinated work between the processor and the accelerator and to further enhance the speed of digital signal processing through the introduction of the accelerator. An overview and comparison of the status of domestic and foreign research are presented in the vein of VR teaching and the overall development of English teaching. Then, the problems and hypotheses to be explored in this study are presented, and several types of research methods used to explore the solutions to the problems are introduced. The results of the two classroom formats were compared, and specific performance data were obtained. The analysis of the results showed that the students in the VR scenario teaching group made greater progress in vocabulary judgments, complementary dialogues, and Chinese to English translation, with a 43% merit rate and a 100% pass rate in English for the whole group. The real-life scenarios created through VR technology greatly increased students’ interest in learning and significantly improved the effectiveness of classroom teaching. The development trend of education informatization is towards virtualization and intelligence, and the application of VR to the process of education teaching is of great significance to promote the modernization of secondary education informatization.